HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR PKn SISWA SMA NEGERI SIPAHUTAR TAPANULI UTARA - Lukman Pardede; Dewi Lestari Pardede (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
The study was conducted to determine the significant relationship between emotional intelligence and Civics learning outcomes of students of SMA Negeri Sipahutar Tapanuli Utara in 2020. This type of research is correlational descriptive. The population in this study is all students of SMA Negeri Sipahutar Tapanuli Utara, consisted of 117 students. The sample used in this study is by using Krecji Table Sampling with a total of 5% of the total population so that the number of samples is 90 people. The instrument in this study is a questionnaire consisting of 34 items that had 4 options (a, b, c, d) which have been tested for validity and reliability. The results of the normality test results of students' emotional intelligence data are normally distributed with the results of the calculation of x2hitung <x2table (59.175> 516). Normality data of student learning outcomes is normally distributed with the results of the calculation of x2hitung <x2tabel (2,225> 516). The results of the linearity test of emotional intelligence data with Civics learning outcomes are linear with the equation Y = 0.535 +0.878 with Fhabel obtained Fh> Ft (Fh> Ft (27.73> 4.20. Tendency test of students' emotional intelligence (Y) is categorized as moderate 31.11 %. `Civics learning outcomes of students (Y) category tends to be moderate (28.88%. The results of the product moment correlation test obtained are (rcount 0.446) and r table = 0.207 then r count> r table (0.446> 0.207), then this shows that there is a significant relationship between emotional intelligence and Civics learning outcomes of students of SMA Negeri Sipahutar Tapanuli Utara in 2020. To test the significance level of the two variables above followed by a statistical test (t test), it is obtained tcount = 4.674 and t table = 1.661 then tcount> ttable, (4,674>, 1,661) because tcount> ttable, this shows that there is a significant relationship between emotional intelligence and Civics learning outcomes of Sipahutar Tapanuli Utara Senior High School students in 2020, the hypothesis is accepted.